2016
DOI: 10.1007/s00018-016-2272-4
|View full text |Cite
|
Sign up to set email alerts
|

Stress transgenerationally programs metabolic pathways linked to altered mental health

Abstract: Stress is among the primary causes of mental health disorders, which are the most common reason for disability worldwide. The ubiquity of these disorders, and the costs associated with them, lends a sense of urgency to the efforts to improve prediction and prevention. Down-stream metabolic changes are highly feasible and accessible indicators of pathophysiological processes underlying mental health disorders. Here, we show that remote and cumulative ancestral stress programs central metabolic pathways linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 66 publications
1
43
0
Order By: Relevance
“…The effects observed on these tasks are robust, consistent and highly reproducible. MSUS is currently one of the few available mouse models of transgenerational epigenetic inheritance with transmission up to the 4th generation, a depth of inheritance previously demonstrated in rodents with prenatal stress [ 57 ], toxicants [ 9 , 24 ], drugs [ 30 , 58 ] or genetic mutation ( Mtrr hypomorphic) [ 59 ]. Studies of the mechanisms of transgenerational inheritance are expected to have important implications for public health in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The effects observed on these tasks are robust, consistent and highly reproducible. MSUS is currently one of the few available mouse models of transgenerational epigenetic inheritance with transmission up to the 4th generation, a depth of inheritance previously demonstrated in rodents with prenatal stress [ 57 ], toxicants [ 9 , 24 ], drugs [ 30 , 58 ] or genetic mutation ( Mtrr hypomorphic) [ 59 ]. Studies of the mechanisms of transgenerational inheritance are expected to have important implications for public health in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious consequences of prenatal maternal stress not only affect the first generation of newborns, but also may be transmitted across subsequent generations (24,25). In fact, recent animal studies have shown that gestational stress across generations has downstream effects on the endocrine and metabolic pathways (26,27). Importantly, intergenerational maternal stress gradually shortens the length of gestation (26) and affects physiological and molecular processes in both the mother and offspring (28).…”
Section: Introductionmentioning
confidence: 99%
“…In the human environment, PS may be particularly impactful in low socioeconomic status communities (Farah 2017), where such stress can occur across generations, consistent with the cyclical nature of poverty. A series of studies in rats (Kiss et al 2016;McCreary et al 2016) mimicked this feature of the human environment by imposing PS consisting of restraint stress and forced swimming in a semi-random sequence in an F0, F1, and F2 generation and subsequently examined multiple consequences in female F3 offspring. Under these conditions, increases in basal corticosterone levels were seen across generations, with almost 2-fold increases between the F2 and F3 generations.…”
Section: Introductionmentioning
confidence: 99%